Complex failure analysis of a cable-roofed stadium structure based on diagnostics and tests. (September 2019) - Kmet, Stanislav; Tomko, Michal; Soltys, Robert; Rovnak, Marian; Demjan, Ivo
Abstract: Results of comprehensive failure-related diagnostics, non-destructive and destructive tests, geodetic surveying, numerical modelling, time-dependent nonlinear static analysis and reliability assessment of a stadium structure with a suspension cable roof in the form of hyperbolic paraboloid cable net after fifty years of operation are presented in the paper. The main goal is the determination of the current degree of damage and resistance of the structure. Results of the metallographic analysis confirmed that the upper layers of the steel wires of carrying and stabilizing cables which were in contact with condensed moisture in the areas of the roof located above the ice surface are damaged by atmospheric corrosion. Current resistances of the diminished cable members obtained by tension tests and their creep constitutive equations are characterized. The geodetic surveying of the selected nodes of the cable net confirmed the significant change of the initial geometry of the cable structure subjected to corrosion and creep over a period of fifty years. Results obtained by time-dependent nonlinear finite element analysis considering rheological phenomena (shrinkage, creep and degradation of mechanical properties) affecting concrete arches and reliability assessment of the cable net with current properties showed that the reliability conditions are not fulfilled, preventing the cables from safely performing its function and consequently requiring the replacement of the cable net with a new cable structure exhibiting the required properties. Highlights: Results of the failure analysis of a stadium structure with cable roof are presented. Metallographic analyses confirmed that cables are damaged by atmospheric corrosion. Geometrical changes of the cable net due to the corrosion and creep were observed. Results from the time-dependent nonlinear FE analysis of the cable net are discussed. Assessment of the cable net showed that the reliability conditions are not fulfilled.